2013
DOI: 10.7314/apjcp.2013.14.5.2771
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality of Life of Breast Cancer Patient Next-of-kin in Turkey

Abstract: Introduction: Quality of life (QoL) issues are of importance in relatives of women with breast cancer (BC)as caregivers in neglecting their own needs due to care of a patient and also as women regarding the potential risk of themselves developing BC. The objectives in the present study were to compare the QoL of female relatives of women in treatment for breast cancer. To date, no study had examined multi-dimensional QoL in accompanying people as compared them into two groups of female relatives whose first de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Moreover, the results of the current study confirmed a mixed relationship between adjuvant therapy and QOL. Women who received chemotherapy or hormonal therapy had lower QOL scores in physical function, role emotional, mental health, and bodily pain than women who did not receive either type of therapy, which is consistent with results from Saudi Arabia [17], Bahrain [26], Malaysia [33], USA [56], Netherlands [55] and Germany [54]. Most of the QOL scores of conservative surgery participants were associated with both better global quality of life and better physical, role physical and social functioning [33,47,55,56].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, the results of the current study confirmed a mixed relationship between adjuvant therapy and QOL. Women who received chemotherapy or hormonal therapy had lower QOL scores in physical function, role emotional, mental health, and bodily pain than women who did not receive either type of therapy, which is consistent with results from Saudi Arabia [17], Bahrain [26], Malaysia [33], USA [56], Netherlands [55] and Germany [54]. Most of the QOL scores of conservative surgery participants were associated with both better global quality of life and better physical, role physical and social functioning [33,47,55,56].…”
Section: Discussionsupporting
confidence: 77%
“…Like other studies [33,54,55], the type of surgery significantly impacted QOL as measured by the SF-36, PF; this was the only QOL measure significantly impacted by the type of surgery. Moreover, the results of the current study confirmed a mixed relationship between adjuvant therapy and QOL.…”
Section: Discussionsupporting
confidence: 55%
“…In their study conducted to assess family caregivers' stress arising from their caregiver roles, Gopalan and Brannon (2006) determined that caregivers had not only physical problems such as hypertension and impaired immune system but also mental health problems such as depression or anxiety. Caregivers, due to their caregiver roles, also develop physical problems such as indigestion, changes in appetite, irregular eating habits, headaches, chronic fatigue, weight gain or loss, muscle pain, difficulty in concentration, and emotional symptoms such as restlessness, insomnia, decreased self-esteem and social isolation (Deeken et al, 2003;Dewar et al, 2004;Tsigaroppoulos et al, 2009;Chang et al, 2013;Ogce et al, 2013;Stajduhar, 2013, Ugur et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients who are treated with RT for breast cancer develop some degree of radiation dermatitis, ranging from mild or brisk erythema to severe moist desquamation (Harper et al, 2004), and severe reactions can impair the quality of life due to pain and lead to interruption of treatment that may be prejudicial to local control (Duncan et al, 1996, Hymes et al, 2006, Pourhoseingholi et al, 2008, Ogce et al, 2013.…”
Section: Introductionmentioning
confidence: 99%